Eksistensi dan Tanggung Jawab Majelis Ulama Indonesia dalam Penerapan Sertifikasi dan Labelisasi Halal Produk Pangan di Indonesia - Renny Supriyatni (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2011)
Halal certification is done to assure halal status of a product. Hence, it can pacify consumers who consume it. The issue of food for Muslims in not only should be healthy, but also must be halal, and appropriate with the guidance of Sharia. Therefore, it takes a special institutions of reviewing and overseeing halal products to be consumed by Muslims, including the Indonesian Ulama Council (MUI). The MUI existence and responsibility is needed, especially in terms of the application and certification of halal labeling of food products in IndonesiaDOI: 10.15408/aiq.v3i2.2140